2018
DOI: 10.1111/ajco.12980
|View full text |Cite
|
Sign up to set email alerts
|

FISH analysis of selected soft tissue tumors: Diagnostic experience in a tertiary center

Abstract: Our study confirms that paraffin FISH is a sensitive and specific ancillary tool in the diagnosis of BST neoplasms when used in the appropriate clinicopathological context. These findings highlight the need for further ancillary molecular tools in the diagnosis and characterization of challenging cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 56 publications
1
14
0
Order By: Relevance
“…The standard test for the diagnosis of SS has been genomic tests to detect the SS18-SSX gene fusion by FISH or RT-PCR [ 13 ], which have reported to be highly specific tests. However, several studies suggested the relatively low sensitivity (83–94%) of these techniques [ 16 , 17 ] and their technical and cost-related issues [ 13 ]. Alternatively, IHC of transducing-like enhancer split 1 (TLE1) has been recognized to distinguish SS from other soft tissue malignancies [ 3 , 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…The standard test for the diagnosis of SS has been genomic tests to detect the SS18-SSX gene fusion by FISH or RT-PCR [ 13 ], which have reported to be highly specific tests. However, several studies suggested the relatively low sensitivity (83–94%) of these techniques [ 16 , 17 ] and their technical and cost-related issues [ 13 ]. Alternatively, IHC of transducing-like enhancer split 1 (TLE1) has been recognized to distinguish SS from other soft tissue malignancies [ 3 , 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…While considered ‘gold standards’ for confirmation of the diagnosis of SS, these ancillary techniques are not perfect. For example, although highly specific, RT–PCR and SS18 break‐apart FISH have had reported sensitivities as low as 94 and 83%, respectively, in some series 10,11 . The primer sets used in RT–PCR may not detect unusual or rare variant transcripts, and SS18 break‐apart FISH may show atypical results in up to 11% of cases 12 .…”
Section: Introductionmentioning
confidence: 99%
“…However, other approaches including RT-PCR and, increasingly, massive parallel sequencing, are being more widely used [ 75 ]. Although highly specific, RT-PCR and SS18 break-apart FISH that are not perfect and have had reported sensitivities as low as 94% and 83%, respectively [ 76 , 77 ]. The use of both techniques has been recommended in the ancillary diagnosis of SS, giving at least 96% sensitivity and 100% specificity [ 55 ].…”
Section: Genomic Featuresmentioning
confidence: 99%